2013
DOI: 10.3390/ijerph10041392
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccumulation of Trace Elements in Ruditapes philippinarum from China: Public Health Risk Assessment Implications

Abstract: The Manila clam Ruditapes philippinarum is one of the most important commercial bivalve species consumed in China. Evaluated metal burden in bivalve molluscs can pose potential risks to public health as a result of their frequent consumption. In this study, concentrations of 10 trace elements (Cu, Zn, Mn, Se, Ni, Cd, Cr, Pb, Hg and As) were determined in samples of the bivalve Ruditapes philippinarum, collected from nine mariculture zones along the coast of China between November and December in 2010, in order… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 35 publications
2
11
0
Order By: Relevance
“…Similar results were found for R. decussatus (0.15-0.95 kg) and R. philippinarum (0.08-0.81 kg), collected from the Ria de Aveiro, Óbidos lagoon (Velez et al, 2015a(Velez et al, , 2015b and from the coast of China (Yang et al, 2013), to exceed the PTWI for As.…”
Section: Dietary Risk Assessmentsupporting
confidence: 87%
“…Similar results were found for R. decussatus (0.15-0.95 kg) and R. philippinarum (0.08-0.81 kg), collected from the Ria de Aveiro, Óbidos lagoon (Velez et al, 2015a(Velez et al, , 2015b and from the coast of China (Yang et al, 2013), to exceed the PTWI for As.…”
Section: Dietary Risk Assessmentsupporting
confidence: 87%
“…In Portugal around 58 kg/cap/year of seafood is consumed, being the clams among the most consumed species (Willemsen, 2003;INE, 2013;DGRM, 2014). However, comparing the present results, with other ecosystems, consumers of clams from Ria de Aveiro, Portugal (Velez et al, 2015a,b) and coast of China (Yang et al, 2013) need to eat less amount (0.13 kg and 0.20 kg, respectively) of calms in one week to exceed PTWI for As.…”
Section: Evaluation Of Human Health Risks From Clams Consumptionmentioning
confidence: 46%
“…Also, Yang et al (2013) found higher concentrations of Cu (2.9e5.4 mg kg À1 DW) and lower or similar concentrations of As, Cr, Ni and Pb (0.6e0.9, 0.2 to 0.3, 1.2 to 1.8 and 0.1 mg kg À1 DW, respectively) in R. philippinarum from China (Yang et al, 2013). Higher accumulation of As, Cr, Ni, Pb and Cu by R. philippinarum was previously reported in Atlantic coast, Spain (18.9e64.0, 1.9 to 5.7, 0.15 to 8.7, 0.5 to 2.6 and 8.2e29.0 mg kg À1 DW) and Venice lagoon, Italy (12.6e32.2,9.6 to 35.5,0.4 to 1.9 and 5.1e26.0 mg kg À1 DW) by Usero et al (1997) and Sfriso et al (2008), respectively.…”
Section: Concentration Of Elementsmentioning
confidence: 97%
“…Cd in fish species from Qinhuangdao had higher concentrations than that from Huilai, the Pearl River Estuary, Zhejiang and Haikou . Yang et al (2013) also showed that along the coast of China, Qinhuangdao was one of the hotspots for the trace element contamination in bivalve R. philippinarum.…”
Section: The Situation Of Different Areasmentioning
confidence: 93%
“…This showed that the economic mollusks were polluted to some extent. Hazard quotients of As, Cd, Cr, Cu, Ni, Pb and Zn in fish species and bivavel R. philippinarum collected from Qinhuangdao were all less than 1, manifesting there was no obvious health risk from the intake of these marine organisms (Yang et al, 2013;. A survey made a historical comparison of concentrations in marine organisms and demonstrated that the concentrations of As, Cd, Hg and Pb in most benthic mussel samples collected from the Bohai Sea showed a decreasing trend or remained steady (Liu et al, 2011c).…”
Section: The Situation Of Different Metalsmentioning
confidence: 96%